A Single-Arm, Open-Label, Pilot, and Feasibility Study of a High Nicotine Strength E-Cigarette Intervention for Smoking Cessation or Reduction for People With Schizophrenia Spectrum Disorders Who Smoke Cigarettes. Issue 7 (16th March 2021) - Caponnetto, Pasquale; DiPiazza, Jennifer; Kim, Jason; Maglia, Marilena; Polosa, Riccardo
Abstract: Introduction: An estimated 60%–90% of people with schizophrenia smoke, compared with 15%–24% of the general population, exacerbating the already high morbidity and mortality rates observed in this population. Aims and Methods: This study aimed to assess the feasibility of using a new-generation high strength nicotine e-cigarette to modify smoking behavior in individuals with schizophrenia spectrum disorders who smoke cigarettes. A single-arm pilot study was conducted with 40 adults with schizophrenia spectrum disorders who smoked and did not intend to reduce or quit smoking. Participants were given a 12-week supply of a JUUL e-cigarette loaded with a 5% nicotine pod. The primary outcome was smoking cessation at week 12. Additional outcomes included: smoking reduction, continuous abstinence at week 24, adoption rate, adherence to the e-cigarette, feasibility, acceptability, and subjective effects. Results: Sixteen (40%) participants quit by the end of 12 weeks. For the whole sample, we observed an overall, sustained 50% reduction in smoking or smoking abstinence in 37/40 (92.5%) of participants and an overall 75% reduction in median cigarettes per day from 25 to six was observed by the end of the 12 weeks ( p < .001). Conclusions: A high strength nicotine e-cigarette has the potential to help people with schizophrenia spectrum disorders to quit or reduce smoking. Further research with a larger sample and a comparator group is needed. The results provide useful information and direction to augment the existing body of knowledge on smoking cessation for people with schizophrenia spectrum disorders. Implications: Considering that most people with schizophrenia spectrum disorders continue smoking, alternative and efficient interventions to reduce or prevent morbidity and mortality are urgently needed. This study showed that adults who smoke and were not motivated to quit, when provided a new-generation e-cigarette with high nicotine content, demonstrated substantially decreased cigarette consumption without causing significant side effects. Although not specifically measured in this study, nicotine absorption in new-generation devices has been shown to be consistently superior compared with the first generation of e-cigarette devices, and this may help explain the lower quit rates in studies using earlier generation devices.